Biosurfactant of acinetobacter calcoaceticus імv в–7241: influence of Cu2+ on synthesis and use in bioremediation processes - Andrushchenko, Yaroslav; Konon, Anastasia; Antoniuk, Svitlana; Pirog, Tatiana (My University, 2012)
The influence of Cu2+ on surfactant synthesis by Acinetobacter calcoaceticus IMV B-7241 and possibility of their using for the degradation of complex oil pollution of soil and water was studied
Keywords: synthesis; синтез; кафедра біотехнології і мікробіології